Front Cover: Synthesis of C37‐Alkenones for Past Climate Reconstructions (Eur. J. Org. Chem. 24/2020). Issue 24 (15th June 2020) - Berton, Giacomo; Pizzini, Sarah; Fabris, Fabrizio; Bertolin, Tommaso; Pafumi, Eugenia; Ceccon, Leonardo; Daelemans, Jonas; Borsato, Giuseppe; Scarso, Alessandro; Piazza, Rossano; Ferretti, Patrizia
Abstract : The Front Cover shows three C37 methyl‐alkenones with different degrees of unsaturation synthesized by marine organisms in relative amounts according to temperature and salinity conditions. Since these molecules are particularly resistant to degradation, they can be observed in marine sediments and their relative amounts are indicative of changes in oceans and climate during the Cenozoic Era. This manuscript describes the total synthesis of these substances, as required for chromatographic standards, as well as the synthesis of their 13 C‐labelled analogues, which enable quality assurance and control procedures. The authors thank Thomas Bassano for creating the artwork. More information can be found in the Full Paper by F. Fabris et al.